Cation-disorder zinc blende Zn0.5Ge0.5P compound and Zn0.5Ge0.5P–TiC–C composite as high-performance anodes for Li-ion batteries. Issue 14 (24th March 2021) - Liu, Guoping; Zhang, Lei; Zhou, Yucun; Soule, Luke; Mu, Yangchang; Li, Wenwu; Shi, Zhicong
Abstract : Zn0.5 Ge0.5 P shows superior crystal and band structure as anode material for lithium-ion batteries, and Zn0.5 Ge0.5 P–TiC–C exhibits excellent electrochemical performance. Abstract : Designing a novel anode material with suitable elemental composition and bonding structure for improving the limited capacity and poor lithium-ion conductivity of lithium-ion batteries (LIBs) is still challenging. Here, guided by first-principles calculations, we report a higher crystal symmetric, cation-disordered zinc blende Zn0.5 Ge0.5 P anode material with high-capacity and high-rate capability owing to superior electron and lithium-ion transport compared to the parent allotrope chalcopyrite ZnGeP2 . The Zn0.5 Ge0.5 P anode exhibits a large specific capacity of 1435 mA h g −1 with a high initial Coulombic efficiency of 92%. An amorphization–conversion–alloying reaction mechanism is proposed based on ex situ characterizations including X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and Raman spectroscopy. During lithiation, the material phase-changes through Li3 P, LiZnGe, β-Li2 ZnGe, and α-Li2 ZnGe intermediates that provide suitable transport channels for fast diffusion of lithium ions. During delithiation, LiZn, Li15 Ge4, and Li3 P nanoparticles reassemble into Zn0.5 Ge0.5 P. A Zn0.5 Ge0.5 P–TiC–C composite with finer particle size and enhanced electronic conductivity exhibits an initial specific capacity of 1076 mA h g −1 and a capacity retention of 92.6% after 500 cycles.